Reynoutrin Improves Ischemic Heart Failure in Rats Via Targeting S100A1 - Wenkai Yang; Hanjian Tu; Kai Tang; Haozhong Huang; Shi Ou; Jianguo Wu (Frontiers Media S.A., 2021)
This study investigated the effects of reynoutrin on the improvement of ischemic heart failure (IHF) and its possible mechanism in rats. The rat heart failure model was established by permanently ligating the left anterior descending coronary artery (LAD) and administering different doses of reynoutrin. Cardiac function, inflammatory factors releasing, oxidative stress, cardiomyocytes apoptosis, and myocardial fibrosis were evaluated. Western blotting was used to determine protein expression levels of S100 calcium-binding protein A1 (S100A1), matrix metallopeptidase 2(MMP2), MMP9, phosphorylated (p-) p65, and transforming growth factor -β1 (TGF-β1) in myocardial tissue of the left ventricle. Results showed that reynoutrin significantly improved cardiac function, suppressed the release of inflammatory factors, reduced oxidative stress, inhibited cardiomyocytes apoptosis, and attenuated myocardial fibrosis in rats with IHF. In rat myocardial tissue, permanent LAD-ligation resulted in a significant down-regulation in S100A1 expression, whereas reynoutrin significantly up-regulated S100A1 protein expression while down-regulating MMP2, MMP9, p-p65, and TGF-β1 expressions. However, when S100A1 was knocked down in myocardial tissue, the above-mentioned positive effects of reynoutrin were significantly reversed. Reynoutrin is a potential natural drug for the treatment of IHF, and its mechanism of action involves the up-regulation of S100A1 expression, thereby inhibiting expressions of MMPs and the transcriptional activity of nuclear factor kappa-B.